2018
DOI: 10.1103/physrevb.97.241115
|View full text |Cite
|
Sign up to set email alerts
|

Attractive Coulomb interactions in a triple quantum dot

Abstract: Electron pairing due to a repulsive Coulomb interaction in a triple quantum dot (TQD) is experimentally studied. It is found that electron pairing in two dots of a TQD is mediated by the third dot, when the third dot strongly couples with the other two via Coulomb repulsion so that the TQD is in the twofold degenerate ground states of (1, 0, 0) and (0, 1, 1) charge configurations. Using the transport spectroscopy that monitors electron transport through each individual dot of a TQD, we analyze how to achieve t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The Coulomb interaction between electrons is known to be repulsive. However, in a variety of systems with electronic degrees of freedom it has been found that an effective attraction between electrons arises, contrary to naive expectations [23][24][25][26] . It is believed that high-temperature superconductivity can be achieved via an effective attractive interaction mediated by Coulomb repulsion 23 .…”
Section: Introductionmentioning
confidence: 70%
“…The Coulomb interaction between electrons is known to be repulsive. However, in a variety of systems with electronic degrees of freedom it has been found that an effective attraction between electrons arises, contrary to naive expectations [23][24][25][26] . It is believed that high-temperature superconductivity can be achieved via an effective attractive interaction mediated by Coulomb repulsion 23 .…”
Section: Introductionmentioning
confidence: 70%
“…The excess energy ∆ε = ε 2 s − ε 1 s , required for the electrons to tunnel from S 1 to S 2 is extracted from the reservoir G via Coulomb coupling. Coming to the fabrication feasibility of such a system, due to the recent progress in in nano-fabrication techniques, coupled systems employing multiple (more than two) quantum dots, with and without Coulomb coupling, have already been experimentally realized [39][40][41][42][43][44]. In addition, it has been experimentally demonstrated that spatially and electrically isolated quantum dots may be bridged to obtain strong Coulomb coupling, in addition to excellent thermal insulation [45][46][47][48][49].…”
Section: Proposed Design and Transport Formulationmentioning
confidence: 99%
“…A single-electron transistor (SET) [7] is a phase-coherent conductor that provides a platform for single-electron tunneling, such as the Coulomb blockade [7][8][9][10][11][12][13][14][15] and the spin blockade [16][17][18], and quantum computation with semiconductor quantum dots (QDs) [19][20][21][22][23][24][25][26][27][28]. It comprises a source (electrode), a drain (electrode), two tunnel junctions, and a quantum dot (a conductive island).…”
Section: Introductionmentioning
confidence: 99%